Creating Professional Learning Communities in a Traditional Educational Leadership Preparation Program - Gini Doolittle; H. Mark Stanwood; Herb Simmerman (Educational Considerations, 2006)
During its 50-year history, the University Council for Educational Administration (UCEA) has witnessed both the development and subsequent demise of innovations in leadership preparation programs.